Toner, toner cartridge, image forming apparatus

By formulating toner with specific adhesion strengths for titanium oxide and silica additives, the toner remains stable in image formation devices, preventing image defects and white streaks, thus ensuring high-quality image reproduction.

JP7627171B2Active Publication Date: 2025-02-05TOSHIBA TEC KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021083104
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-17
Publication Date
2025-02-05
Estimated Expiration
2041-05-17

AI Technical Summary

Technical Problem

The reuse of toner with detached external additives in image formation devices leads to changes in charging properties, causing issues such as image defects and white streaks due to accumulation in the developer.

Method used

The toner formulation includes toner mother particles with specific adhesion strengths for both titanium oxide and silica additives, ensuring they remain attached to the surface within defined ranges, using crystalline polyester resin and ester wax to maintain low-temperature fixing and heat resistance.

Benefits of technology

The solution prevents image defects and white streaks by maintaining toner fluidity and charge stability, even when reused, enhancing image quality and device performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627171000002
    Figure 0007627171000002
  • Figure 0007627171000003
    Figure 0007627171000003
  • Figure 0007627171000004
    Figure 0007627171000004
Patent Text Reader

Abstract

To provide a toner that substantially suppresses occurrence of an image defect even when the same is reused, a toner cartridge that stores the toner, and an image forming apparatus.SOLUTION: A toner of an embodiment has a toner base particle and an external additive. The toner base particle includes a binder resin, ester wax, and a coloring agent. The external additive includes titanium oxide and silica. Adhesive strength A of the external additive to the toner base particle according to a following formula (1) is 90-100%. Adhesive strength B of the external additive to the toner base particle according to a following formula (2) is 50-80%. Formula (1): adhesive strength A=(Ia2 / Ia1)×100. Formula (2): adhesive strength B=(Ib2 / Ib1)×100. Ia1: X-ray intensity of titanium in toner. Ia2: X-ray intensity of titanium in a particle A obtained by a specific processing method. Ib1: X-ray intensity of silicon in toner. Ib2: X-ray intensity of silicon in a particle B obtained by the specific processing method.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] An embodiment of the present invention relates to a toner, a toner cartridge, and an image forming apparatus. [Background technology]

[0002] 2. Description of the Related Art In electrophotographic image forming apparatuses, it has been proposed to recover toner remaining on a photoconductor after transfer and to return the recovered toner to a developing device for reuse (for example, Patent Documents 1 and 2). However, when the toner remaining on the photoconductor is reused, the toner from which the external additives have been removed may be re-supplied to the developing device. The chargeability of the toner from which the external additives have been removed changes. Therefore, if the toner from which the external additives have been removed accumulates in the developing device, there is a problem that image defects such as image fogging and white streaks are likely to occur. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2002-214823 A [Patent Document 2] JP 2002-296829 A Summary of the Invention [Problem to be solved by the invention]

[0004] The problem to be solved by the present invention is to provide a toner which is unlikely to cause image defects even when reused, and a toner cartridge and an image forming apparatus in which the toner is contained. [Means for solving the problem]

[0005] The toner of the embodiment has toner base particles and an external additive. The external additive is attached to the surface of the toner base particles. The toner base particles contain a binder resin, an ester wax, and a colorant. The external additive contains titanium oxide and silica. The adhesion strength A of the external additive to the toner base particles is 90 to 100%. The adhesion strength A is calculated by the following formula (1). The adhesion strength B of the external additive to the toner base particles is 50 to 80%. The adhesion strength B is calculated by the following formula (2). Adhesion strength A = (I a2 / I a1 )×100 Equation (1) In formula (1), I a1 is the X-ray intensity of titanium measured for the toner of the embodiment; I a2 is the X-ray intensity of titanium measured for particle A obtained by method A described below. Method A: The aqueous liquid containing the toner and water is shaken for 5 minutes under conditions of 25° C. and 200 rpm, the external additives that have been desorbed are removed by centrifugation, and the particles obtained by drying are designated as particles A. Adhesion strength B = (I b2 / I b1 )×100 Formula (2) In formula (2), I b1 is the X-ray intensity of silicon measured for the toner of the embodiment; I b2 is the X-ray intensity of silicon measured for particle B obtained by method B described below. Method B: An aqueous liquid containing the toner of the embodiment and water is subjected to ultrasonic treatment under conditions of 25° C., 28 kHz, and 55 W, the detached external additives are removed by centrifugation, and the particles obtained by drying are designated as particles B. [Brief description of the drawings]

[0006] [Figure 1] 1 is a diagram illustrating an example of a schematic structure of an image forming apparatus according to an embodiment; [Diagram 2] FIG. 2 is a perspective view of a developing device of the image forming apparatus of FIG. [Diagram 3] 2 is a side view of a developing device of the image forming apparatus of FIG. 1. [Figure 4]FIG. 13 is a diagram illustrating an example of a schematic structure of an image forming apparatus according to another embodiment. [Diagram 5] 5 is a perspective view of a modified example of the developing device of the image forming apparatus in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The toner according to the embodiment will be described below. The toner of the embodiment includes toner base particles and an external additive. In the toner of the embodiment, the adhesion strength A and adhesion strength B of the external additive to the toner base particles are within a specific range. Therefore, image defects such as image fogging and white streaks are unlikely to occur. The adhesion strength A and adhesion strength B will be described later.

[0008] The toner base particles will now be described. The toner base particles of the embodiment include a binder resin, an ester wax, and a colorant. The toner base particles of the embodiment may further include other components in addition to the binder resin, the ester wax, and the colorant as long as the effects disclosed in the embodiment are obtained.

[0009] The binder resin will now be described. At least a part of the binder resin is preferably a crystalline polyester resin. That is, it is preferable to use a crystalline polyester resin and a binder resin other than the crystalline polyester resin in combination as the binder resin. When at least a part of the binder resin is a crystalline polyester resin, the low temperature fixability of the toner is improved.

[0010] The crystalline polyester resin will now be described. The crystalline polyester resin functions as a binder resin. In the embodiment, a polyester resin having a ratio of softening temperature to melting temperature (softening temperature / melting temperature) of 0.8 to 1.2 is called a "crystalline polyester resin". A polyester resin having a ratio of softening temperature to melting temperature (softening temperature / melting temperature) of less than 0.8 or more than 1.2 is called a "non-crystalline polyester resin".

[0011] Examples of the crystalline polyester resin include condensation polymers of divalent or higher alcohols and divalent or higher carboxylic acids. Examples of the dihydric or higher alcohol include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 1,4-butenediol, polyoxypropylene, polyoxyethylene, glycerin, pentaerythritol, trimethylolpropane, etc. As the dihydric or higher alcohol, 1,4-butanediol and 1,6-hexanediol are preferred. Examples of the divalent or higher carboxylic acid include adipic acid, oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, phthalic acid, isophthalic acid, terephthalic acid, sebacic acid, azelaic acid, succinic acid substituted with an alkyl group or an alkenyl group, cyclohexanedicarboxylic acid, trimellitic acid, pyromellitic acid, acid anhydrides thereof, and esters thereof. Examples of succinic acid substituted with an alkyl or alkenyl group include succinic acid substituted with an alkyl or alkenyl group having 2 to 20 carbon atoms. Examples include n-dodecenyl succinic acid, n-dodecyl succinic acid, etc. As the divalent or higher carboxylic acid, fumaric acid is preferred. However, the crystalline polyester resin is not limited to the condensation polymer of the divalent or higher alcohol and the divalent or higher carboxylic acid exemplified here. The crystalline polyester resin may be used alone or in combination of two or more kinds.

[0012] The mass average molecular weight of the crystalline polyester resin is 6×10 3 ~18×10 3 is preferred, 8×10 3 ~14×10 3When the mass average molecular weight of the crystalline polyester resin is equal to or more than the lower limit, the low temperature fixability of the toner is improved. When the mass average molecular weight of the crystalline polyester resin is equal to or less than the upper limit, the toner has excellent storage stability and low temperature offset resistance. In this specification, the mass average molecular weight is a value calculated as polystyrene by gel permeation chromatography.

[0013] The melting point of the crystalline polyester resin is preferably 60 to 120° C., more preferably 70 to 115° C., and even more preferably 80 to 110° C. When the melting point of the crystalline polyester resin is equal to or higher than the lower limit, the toner has excellent storage stability and heat resistance. When the melting point of the crystalline polyester resin is equal to or lower than the upper limit, the toner has improved low-temperature fixability. The melting point of the crystalline polyester resin can be measured, for example, by a differential scanning calorimeter (DSC).

[0014] Other binder resins will now be described. Examples of the other binder resin include non-crystalline polyester resin, styrene-based resin, ethylene-based resin, acrylic-based resin, phenol-based resin, epoxy-based resin, allyl phthalate-based resin, polyamide-based resin, maleic acid-based resin, etc. However, the other binder resin is not limited to these examples. The other binder resins may be used alone or in combination of two or more.

[0015] The other binder resin is preferably a non-crystalline polyester resin, since the effects disclosed in the embodiment can be easily obtained. Examples of the non-crystalline polyester resin include a condensation polymer of a divalent or higher carboxylic acid and a divalent alcohol. Examples of divalent or higher carboxylic acids include divalent or higher carboxylic acids, acid anhydrides of divalent or higher carboxylic acids, esters of divalent or higher carboxylic acids, etc. Examples of esters of divalent or higher carboxylic acids include lower alkyl (carbon number 1 to 12) esters of divalent or higher carboxylic acids. Examples of dihydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, bisphenol A, hydrogenated bisphenol A, and alkylene oxide adducts of bisphenol A. However, the dihydric alcohol is not limited to these examples. Examples of the alkylene oxide adduct of bisphenol A include compounds in which an average of 1 to 10 moles of alkylene oxide having 2 to 3 carbon atoms is added to bisphenol A. Examples of the alkylene oxide adduct of bisphenol A include polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene (3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene (2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene (2.0)-polyoxyethylene (2.0)-2,2-bis(4-hydroxyphenyl)propane, and polyoxypropylene (6)-2,2-bis(4-hydroxyphenyl)propane. The dihydric alcohol is preferably an alkylene oxide adduct of bisphenol A. The dihydric alcohol may be used alone or in combination of two or more kinds.

[0016] The other binder resins can be obtained, for example, by polymerizing a single or multiple kinds of vinyl polymerizable monomers. Examples of the vinyl polymerizable monomer include aromatic vinyl monomers, ester monomers, carboxylic acid-containing monomers, and amine monomers. Examples of aromatic vinyl monomers include styrene, methylstyrene, methoxystyrene, phenylstyrene, chlorostyrene, and derivatives thereof. Examples of the ester monomer include methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, and derivatives thereof. Examples of the carboxylic acid-containing monomer include acrylic acid, methacrylic acid, fumaric acid, maleic acid, and derivatives thereof. Examples of the amine monomer include aminoacrylate, acrylamide, methacrylamide, vinylpyridine, vinylpyrrolidone, and derivatives thereof.

[0017] Other binder resins may be obtained by polycondensation of a polymerizable monomer component consisting of an alcohol component and a carboxylic acid component. In polycondensation of the polymerizable monomer component, various assistants such as a chain transfer agent, a crosslinking agent, a polymerization initiator, a surfactant, a flocculating agent, a pH adjuster, and a defoaming agent may be used.

[0018] The ester wax will be described. The ester wax is an ester compound that functions as a release agent. As the ester wax, the following specific ester wax α is preferred in terms of the heat resistance and storage stability of the toner. Ester wax α: a condensation polymer of a first monomer group consisting of at least three kinds of carboxylic acids and a second monomer group consisting of at least two kinds of alcohols. The ester wax α is composed of two or more types of ester compounds having different carbon numbers.

[0019] Regarding the ester wax α, the first monomer group will be described. The number of types of carboxylic acids in the first monomer group is preferably 7 or less, more preferably 5 or less, and even more preferably 4 or less, in view of easy availability of the ester wax α. Here, the number of carbon atoms of the carboxylic acid having the maximum content in the first monomer group is C n The number of carbon atoms is C n is preferably 19 to 28, more preferably 19 to 24, and further preferably 20 to 24. nWhen the carbon number C is equal to or more than the lower limit, the heat resistance of the ester wax α is improved. n When it is equal to or less than the upper limit, the low temperature fixability of the toner is improved.

[0020] Maximum carbon content C n The proportion of the carboxylic acid is preferably 70 to 95 mass%, more preferably 80 to 95 mass%, and even more preferably 85 to 95 mass%, based on 100 mass% of the first monomer group. n When the ratio of the carboxylic acid is equal to or greater than the lower limit, the maximum peak of the carbon number distribution of the ester wax α tends to be located on the high carbon number side, and therefore the toner has excellent heat resistance and storage stability. n When the ratio of the carboxylic acid is equal to or less than the upper limit, the ester wax α is easily available.

[0021] The ratio of the carboxylic acid having 18 or less carbon atoms in the first monomer group is preferably 0 to 5% by mass, and more preferably 0 to 1% by mass, relative to 100% by mass of the first monomer group. When the ratio of the carboxylic acid having 18 or less carbon atoms is equal to or greater than the lower limit, the ester wax α is easily available. When the ratio of the carboxylic acid having 18 or less carbon atoms is equal to or less than the upper limit, the ratio of the ester compound having a relatively low molecular weight in the ester wax α is reduced. As a result, the toner has excellent heat resistance and storage stability. The content of carboxylic acids having each carbon number in the first monomer group can be measured, for example, by mass spectrometry using FD-MS (Field Desorption Mass Spectrometry) for the product obtained after the methanolysis reaction of the ester wax α.

[0022] As the carboxylic acid in the first monomer group, a long-chain carboxylic acid is preferable because the ester wax α is easily available, and a long-chain alkyl carboxylic acid is preferable. The long-chain carboxylic acid is appropriately selected depending on the characteristics, performance, etc. required for the ester wax α. The long-chain carboxylic acid is preferably a long-chain carboxylic acid having 19 to 28 carbon atoms, and more preferably a long-chain carboxylic acid having 20 to 24 carbon atoms. When the carbon number of the long-chain carboxylic acid is equal to or more than the lower limit, the heat resistance of the ester wax α is improved. When the carbon number of the long-chain carboxylic acid is equal to or less than the upper limit, the low-temperature fixability of the toner is improved. Examples of long-chain alkyl carboxylic acids include palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, and montanic acid.

[0023] Regarding the ester wax α, the second monomer group will be described. The number of types of alcohols in the second monomer group is preferably 5 or less, more preferably 4 or less, and even more preferably 3 or less, in view of easy availability of the ester wax α. Here, the number of carbon atoms of the alcohol having the maximum content in the second monomer group is C m The number of carbon atoms is C m is preferably 19 to 28, more preferably 20 to 24, and further preferably 20 to 22. m When the carbon number C is equal to or more than the lower limit, the heat resistance of the ester wax α is improved. m When it is equal to or less than the upper limit, the low temperature fixability of the toner is improved.

[0024] Maximum carbon content C m The proportion of the alcohol is preferably 70 to 90% by mass, more preferably 80 to 90% by mass, and even more preferably 85 to 90% by mass, based on 100% by mass of the second monomer group. m When the ratio of the alcohol is equal to or greater than the lower limit, the maximum peak of the carbon number distribution of the ester wax α tends to be located on the high carbon number side. Therefore, the toner has excellent heat resistance and storage stability. m When the alcohol ratio is equal to or less than the upper limit, the ester wax α is easily available.

[0025] The proportion of the alcohol having 18 or less carbon atoms in the second monomer group is preferably 20% by mass or less, more preferably 10 to 20% by mass, and even more preferably 15 to 20% by mass, relative to 100% by mass of the second monomer group. When the proportion of the alcohol having 18 or less carbon atoms is equal to or greater than the lower limit, the ester wax α is easily available. When the proportion of the alcohol having 18 or less carbon atoms is equal to or less than the upper limit, the proportion of ester compounds having relatively low molecular weights in the ester wax α is reduced. As a result, the toner has excellent heat resistance and storage stability. The content of alcohols having each carbon number in the second monomer group can be measured, for example, by subjecting the ester wax α to a methanolysis reaction product and subjecting it to mass spectrometry using FD-MS.

[0026] As the alcohol in the second monomer group, a long-chain alcohol is preferable because the ester wax α is easily available, and a long-chain alkyl alcohol is more preferable. The long-chain alcohol is appropriately selected depending on the properties and performance required for the ester wax α. The long-chain alcohol is preferably a long-chain alcohol having 19 to 28 carbon atoms, and more preferably a long-chain alcohol having 20 to 22 carbon atoms. When the carbon number of the long-chain alcohol is equal to or more than the lower limit, the heat resistance of the ester wax α is improved. When the carbon number of the long-chain alcohol is equal to or less than the upper limit, the low-temperature fixability of the toner is improved. Examples of long-chain alkyl alcohols include palmityl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, lignoceryl alcohol, ceryl alcohol, and montanyl alcohol.

[0027] In Ester Wax α, the maximum carbon number C of the ester compounds that make up Ester Wax α is l It is preferable that an ester compound having a carbon number C l is preferably 43 or more, more preferably 43 to 56, still more preferably 43 to 52, particularly preferably 44 to 46, and most preferably 44. l When the number of carbon atoms is equal to or more than the lower limit, the toner has excellent heat resistance and storage stability.l When the amount of the ester wax α is equal to or less than the upper limit, the ester wax α is easily available.

[0028] Carbon number C l The ester compound is represented by the following formula (I): R 1 COOR 2 (I) R in formula (I) 1 and R 2 is an alkyl group. 1 and R 2 The total number of carbon atoms in R is preferably 42 or more, more preferably 42 to 55, still more preferably 42 to 51, particularly preferably 43 to 45, and most preferably 43. 1 and R 2 When the total number of carbon atoms in R is equal to or greater than the lower limit, the toner has excellent heat resistance and storage stability. 1 and R 2 When the total number of carbon atoms of R is equal to or less than the upper limit, the ester wax α is easily available. 1 For example, the carbon number C n The number of carbon atoms in the carboxylic acid is C n It can be controlled by adjusting R 2 For example, the carbon number C m The number of carbon atoms in the alcohol m It can be controlled by adjusting

[0029] Carbon number C l The proportion of the ester compound is preferably 65% ​​by mass or more, more preferably 65 to 90% by mass, further preferably 70 to 90% by mass, and particularly preferably 80 to 90% by mass, based on 100% by mass of the ester wax α. l When the ratio of the ester compound is equal to or more than the lower limit, the maximum peak of the carbon number distribution of the ester wax α becomes sufficiently high, and as a result, the toner has excellent heat resistance and storage stability. Carbon number C l When the proportion of the ester compound is equal to or less than the upper limit, the ester wax α is easily available.

[0030] The carbon number distribution of the ester wax α preferably has only one maximum peak in the region of carbon number 43 or more. In this case, the proportion of ester compounds with relatively low molecular weights is reduced. As a result, the toner has excellent heat resistance and storage stability. In the carbon number distribution of the ester wax α, the position of the maximum peak is preferably in the region of 43 to 56 carbon atoms, more preferably in the region of 44 to 52 carbon atoms, even more preferably in the region of 44 to 46 carbon atoms, and most preferably in the region of 44 carbon atoms. When the position of the maximum peak is in the region of the carbon number equal to or greater than the lower limit, the toner has excellent heat resistance and storage stability. When the position of the maximum peak is in the region of the carbon number equal to or less than the upper limit, the ester wax α is easily available. The content of the ester compounds having each carbon number in the ester wax α can be measured, for example, by mass spectrometry using FD-MS.

[0031] The melting point of the ester wax α is preferably 60 to 85° C., more preferably 65 to 80° C., and even more preferably 65 to 75° C. When the melting point of the ester wax α is equal to or higher than the lower limit, the toner has excellent heat resistance and storage stability. In addition, offset is unlikely to occur in a high-temperature environment. When the melting point of the ester wax α is equal to or lower than the upper limit, the low-temperature fixability of the toner is improved. The melting point of the ester wax α can be measured, for example, as the maximum endothermic peak temperature by differential scanning calorimetry (DSC).

[0032] The ester wax α can be synthesized, for example, by esterifying a long-chain carboxylic acid with a long-chain alcohol. In the esterification reaction, it is preferable to use at least three or more types of long-chain alkyl carboxylic acids and at least two or more types of long-chain alkyl alcohols. The carbon number distribution of the ester compounds contained in the ester wax α can be adjusted by adjusting the carbon numbers of the long-chain alkyl carboxylic acids and the long-chain alkyl alcohols and the amounts of each used. The esterification reaction can be carried out, for example, while heating under a nitrogen stream. The esterification reaction product may be dissolved in a solvent containing ethanol, toluene, etc., and further purified by adding a basic aqueous solution such as an aqueous sodium hydroxide solution to separate the organic layer and the aqueous layer. The aqueous layer is removed to obtain the ester wax α. It is preferable to repeat the purification operation several times.

[0033] The colorant will now be described. The colorant is not particularly limited, and examples thereof include carbon black, cyan, yellow, and magenta pigments, dyes, and the like.

[0034] Examples of carbon black include aniline black, lamp black, acetylene black, furnace black, thermal black, channel black, and ketjen black. Examples of pigments and dyes include Fast Yellow G, Benzidine Yellow, Chrome Yellow, Quinoline Yellow, India Fast Orange, Irgazin Red, Carmine FB, Permanent Bordeaux FRR, Pigment Orange R, Lithol Red 2G, Lake Red C, Rhodamine FB, Rhodamine B Lake, DuPont Oil Red, Phthalocyanine Blue, Pigment Blue, Aniline Blue, Chalcone Blue, Ultramarine Blue, Brilliant Green B, Phthalocyanine Green, Malachite Green Oxalate, Methylene Blue Chloride, Rose Bengal, and Quinacridone.

[0035] Colorants are indicated by color index numbers, for example, CI Pigment Black 1, 6, 7, CI Pigment Yellow 1, 12, 14, 17, 34, 74, 83, 97, 155, 180, 185, CI Pigment Orange 48, 49, CI Pigment Red 5, 12, 31, 48, 48:1, 48:2, 48:3, 48:4, 48:5, 49, 53, 53:1, 53:2, 53:3 , 57, 57:1, 81, 81:4, 122, 146, 150, 177, 185, 202, 206, 207, 209, 238, 269, CI Pigment Blue 15, 15:1, 15:2, 15:3, 15:4, 15:5, 15:6, 75, 76, 79, CI Pigment Green 1, 7, 8, 36, 42, 58, CI Pigment Violet 1, 19, 42, CI Acid Red 52, etc. However, the colorant is not limited to these examples. The colorants may be used alone or in combination of two or more.

[0036] The other ingredients will now be described. Examples of other components include additives such as charge control agents, surfactants, basic compounds, flocculants, pH adjusters, and antioxidants. However, the additives are not limited to these examples. Any one of the additives may be used alone, or two or more of them may be used in combination.

[0037] The charge control agent will now be described. When the toner base particles contain a charge control agent, the toner is easily transferred onto a recording medium such as paper. Examples of the charge control agent include a metal-containing azo compound, a metal-containing salicylic acid derivative compound, a hydrophobic metal oxide, and a polysaccharide clathrate compound. As the metal-containing azo compound, a complex or complex salt in which the metal is iron, cobalt, or chromium, or a mixture thereof is preferable. As the metal-containing salicylic acid derivative compound and the metal oxide hydrophobic metal, a complex or complex salt in which the metal is zirconium, zinc, chromium, or boron, or a mixture thereof is preferable. As the polysaccharide clathrate compound, a polysaccharide clathrate compound containing aluminum (Al) and magnesium (Mg) is preferable.

[0038] Volume average primary particle diameter of toner base particles: D 50 The D of the toner base particles is preferably 4 to 12 μm, and more preferably 5 to 10 μm. 50 When the D of the toner base particles is equal to or larger than the lower limit, the surface area of ​​the toner base particles is easily secured, and the external additive is easily attached to the toner base particles. 50 When the amount of the external additive is equal to or less than the upper limit, adhesion of an excessive amount of the external additive to the toner base particles can be easily suppressed, and therefore, the adhesion strength B described below can be easily controlled within a predetermined range.

[0039] The composition of the toner base particles will be described. The content of the ester wax is preferably 3 to 15% by mass, more preferably 3 to 13% by mass, and even more preferably 5 to 10% by mass, based on 100% by mass of the toner base particles. When the content of the ester wax is equal to or more than the lower limit, the toner has excellent storage stability and heat resistance. When the content of the ester wax is equal to or less than the upper limit, the low-temperature fixability of the toner is improved. Also, the charge amount is easily maintained.

[0040] When the toner base particles contain a crystalline polyester resin, the content of the crystalline polyester resin is preferably 5 to 25% by mass, more preferably 5 to 20% by mass, and even more preferably 5 to 15% by mass, based on 100% by mass of the toner base particles. When the content of the crystalline polyester resin is equal to or more than the lower limit, the low-temperature fixing property of the toner is improved. When the content of the crystalline polyester resin is equal to or less than the upper limit, the toner has even better low-temperature offset resistance and high-temperature offset resistance.

[0041] When the toner base particles contain a non-crystalline polyester resin, the content of the non-crystalline polyester resin is preferably 60 to 90% by mass, more preferably 65 to 85% by mass, and even more preferably 70 to 80% by mass, based on 100% by mass of the toner base particles. When the content of the non-crystalline polyester resin is equal to or more than the lower limit, the toner has better offset resistance. When the content of the non-crystalline polyester resin is equal to or less than the upper limit, the toner has improved low-temperature fixability.

[0042] When the toner base particles contain a colorant, the content of the colorant is preferably 2 to 13% by mass, more preferably 3 to 8% by mass, based on 100% by mass of the toner base particles. When the content of the colorant is equal to or more than the lower limit, the toner has excellent color reproducibility. When the content of the colorant is equal to or less than the upper limit, the dispersibility of the colorant is excellent, and the low-temperature fixability of the toner is improved. In addition, the charge amount of the toner is easily controlled.

[0043] The external additives will be described. The external additive includes titanium oxide and silica. As the titanium oxide, strontium titanate and titanium oxide are preferable. When the external additive further contains either or both of strontium titanate and titanium oxide, the charge amount of the toner is unlikely to be excessively high. In addition, the charge amount distribution of the toner is likely to have a sharp shape. As a result, the amount of toner scattering is suppressed. In addition, the charge amount of the toner is appropriately maintained even at low temperatures.

[0044] Titanium oxide D 50The diameter of the titanium oxide is preferably 5 to 100 nm, more preferably 5 to 50 nm, and even more preferably 10 to 30 nm. 50 When is within the above-mentioned range, the adhesion strength A is likely to be high. Also, the amount of toner scattering is likely to be suppressed. Therefore, stains on members inside the machine, stains on images, and fogging are likely to be reduced.

[0045] Silica is a particle of silicon dioxide. The silica is not particularly limited as long as the adhesion strength B is within a predetermined numerical range. For example, wet silica, calcined silica, and hydrophobic silica can be mentioned, but various kinds of silica other than these examples can be used. Wet silica can be produced, for example, by using sodium silicate made from silica sand as a raw material, neutralizing an aqueous solution containing sodium silicate to precipitate silica, which is then filtered and dried (liquid phase method).In contrast, calcined silica (dry silica) is obtained by reacting silicon tetrachloride in a high-temperature flame. The degree of hydrophobicity of hydrophobic silica can be measured, for example, by the following method. 50 ml of ion-exchanged water and 0.2 g of sample are placed in a beaker, and methanol is dropped from a burette while stirring with a magnetic stirrer. Next, as the methanol concentration in the beaker increases, the powder gradually settles, and the volume percentage of methanol in the mixed solution of methanol and ion-exchanged water at the end point when the entire powder has settled is taken as the degree of hydrophobicity (%).

[0046] Silica D 50 The D of silica is preferably 70 to 120 nm, more preferably 75 to 115 nm, and more preferably 80 to 110 nm. 50 When is equal to or greater than the lower limit, the charge amount of the toner of the embodiment is likely to be maintained high. Also, the adhesive strength B is likely to be high. Silica D 50 When the adhesion strength B is equal to or less than the upper limit, the toner of the embodiment is unlikely to be excessively charged, and therefore a sufficient image density is likely to be maintained.

[0047] The external additive may contain either primary particles of silica or secondary particles of silica. Primary particles of silica refer to a single particle made of silica. Primary particles of silica are preferably spherical, more preferably true spherical. The secondary particles of silica are agglomerates of two or more primary particles of silica. Therefore, the secondary particles are amorphous. The specific shape of the secondary particles is not particularly limited. The shape of the secondary particles may be a polygonal column, a polyhedron, or an ellipsoid.

[0048] The adhesion strength A is calculated by the following formula (1): The adhesion strength A is an index of the strength of adhesion of the external additive to the toner base particles. Adhesion strength A = (I a2 / I a1 )×100 Formula (1)

[0049] In formula (1), I a1 is the X-ray intensity of titanium measured for the toner of the embodiment; I a2 is the X-ray intensity of titanium measured for particle A obtained by method A described below. Method A: The aqueous liquid containing the toner and water is shaken for 5 minutes under conditions of 25° C. and 200 rpm, the external additives that have been desorbed are removed by centrifugation, and the particles obtained by drying are designated as particles A. Regarding the method A, the aqueous liquid may further contain a surfactant. The surfactant is not particularly limited. Any of cationic surfactants, anionic surfactants, amphoteric surfactants, and nonionic surfactants may be used.

[0050] The adhesion strength A is 90 to 100%, preferably 93 to 100%. When the adhesion strength A is equal to or greater than the lower limit, the titanium oxide of the external additive is less likely to be detached from the surface of the toner base particles. Therefore, even when the toner is reused, the titanium oxide is less likely to accumulate in the developer, which prevents deterioration of the chargeability and reduces the occurrence of image fogging.

[0051] Among external additives, titanium oxides such as strontium titanate and titanium oxide have a relatively low chargeability. Therefore, titanium oxides are difficult to transfer to recording media such as paper and difficult to develop. Therefore, in an image forming apparatus equipped with a recycling system, titanium oxides detached from the surfaces of toner base particles are collected in a developing device by a cleaning device. The detached titanium oxides are then accumulated in the developer. When titanium oxides, which have a relatively low chargeability, accumulate in the developer, the chargeability of the developer deteriorates, and the amount of toner with an insufficient charge gradually increases. As a result, image fogging is likely to occur. To address this issue, the present inventors discovered that titanium oxide can be firmly attached to the surface of the toner base particles by first adding titanium oxide to the toner base particles in the external addition step during toner production, and then adjusting the stirring speed, stirring time, external addition temperature, etc. Specifically, the above-mentioned issue can be resolved by setting the above-mentioned adhesion strength A to 90% or more.

[0052] The adhesion strength B is calculated by the following formula (2): The adhesion strength B is an index of the strength of adhesion of the external additive to the toner base particles. Adhesion strength B = (I b2 / I b1 )×100 Formula (2) In formula (2), I b1 is the X-ray intensity of silicon measured for the toner of the embodiment; I b2 is the X-ray intensity of silicon measured for particle B obtained by method B described below. Method B: An aqueous liquid containing the toner of the embodiment and water is subjected to ultrasonic treatment under conditions of 25° C., 28 kHz, and 55 W, the detached external additives are removed by centrifugation, and the particles obtained by drying are designated as particles B.

[0053] The adhesive strength B is 50 to 80%, preferably 55 to 75%, and more preferably 60 to 70%. When the adhesive strength B is equal to or greater than the lower limit, silica among the external additives is less likely to be detached from the surface of the toner base particles. This is believed to improve the heat resistance and storage stability of the toner. When the adhesive strength B is equal to or less than the upper limit, the fluidity of the toner is easily ensured, and therefore, the frictional charging with the carrier in the developer is not easily hindered.

[0054] In an image forming apparatus equipped with a recycling system, silica may be detached from the surface of the toner base particles. In particular, silica is likely to be detached under conditions of use in which there is a rise in temperature or a lot of mechanical stress (e.g., during long-term use, etc.). Therefore, silica is likely to be detached from the surface of the toner base particles in the developer. As a result, the developer may cause caking, which may lead to image defects such as white streaks caused by poor transport. On the other hand, if the adhesion strength of the silica is too strong, there is also a problem that the fluidity of the toner may decrease and image fogging may easily occur. This is because the toner is required to have an appropriate fluidity in terms of the charging property due to contact with the carrier. To address this issue, the present inventors discovered that titanium oxide can be firmly attached to the surface of the toner base particles by adding titanium oxide to the toner base particles before silica in the external addition step during toner production, and adjusting the stirring speed, stirring time, external addition temperature, etc. Specifically, the above-mentioned issue can be resolved by setting the above-mentioned adhesion strength B to 50 to 80%.

[0055] The effect of the adhesive strength A and the adhesive strength B being within the predetermined range becomes remarkable when at least a part of the binder resin is a crystalline polyester resin. When the toner base particles contain a crystalline polyester resin, the toner has excellent low-temperature fixing property. However, the toner containing a crystalline polyester resin may have the following problems. Toners containing crystalline polyester resins with low heat resistance are prone to soft caking at high temperatures. Soft caking toners have low fluidity, which can easily cause problems with developer transport within image forming devices. Toners that contain highly hygroscopic crystalline polyester resins tend to lose charge easily.

[0056] Thus, in a toner containing a crystalline polyester, it is difficult to maintain low-temperature fixing property, fluidity, and charge amount. On the other hand, the use of a general external additive is effective in improving the heat resistance of the toner and maintaining the charge amount. However, when the toner is reused, the toner from which the external additive has been peeled off may be resupplied to the developing device. Therefore, it becomes even more difficult to maintain the heat resistance and the charge amount within an appropriate range. In response to these problems, the toner of the embodiment has adhesion strength A and adhesion strength B within a specified range. Therefore, the heat resistance and fluidity of the toner are appropriately maintained, and transport failure of the developer is unlikely to occur. In particular, since the adhesion strength B is 50 to 80%, the silica adheres to the toner base particles with an appropriate strength. Therefore, the charge amount is unlikely to decrease. It is believed that these effects are achieved even when the toner is reused.

[0057] The external additive may further contain inorganic oxides other than silica, strontium titanate, and titanium oxide, as long as the effects disclosed in the embodiment are obtained. Examples of the inorganic oxides include alumina and tin oxide. The silica particles and the particles made of an inorganic oxide may be surface-treated with a hydrophobizing agent in order to improve stability. The inorganic oxide may be used alone or in combination of two or more kinds.

[0058] The content of the external additive is preferably 2 to 15 parts by mass, more preferably 4 to 10 parts by mass, and even more preferably 4 to 8 parts by mass, relative to 100 parts by mass of the toner base particles. When the content of the external additive is within the above-mentioned numerical range, it is easy to control the adhesion strength A and adhesion strength B within a specific range. In addition, when the content of the external additive is equal to or more than the above-mentioned lower limit, it is easy to ensure the charge amount of the toner. Therefore, it is easy to maintain the charge amount even under high temperature and high humidity conditions, and image defects are further unlikely to occur. When the content of the external additive is equal to or less than the above-mentioned upper limit, it is difficult for the charge amount of the toner to become excessively high. Therefore, it is easy to maintain the charge amount of the toner appropriately.

[0059] The toner manufacturing method will be described. The toner of the embodiment can be produced by mixing the toner base particles with the external additives. By mixing the toner base particles with the external additives, the external additives are attached to the surfaces of the toner base particles. The toner base particles of the embodiment can be produced by, for example, a kneading and pulverizing method or a chemical method.

[0060] The kneading and pulverizing method will be described. The kneading and pulverizing method may, for example, be a production method including the following mixing step, kneading step, and pulverizing step. The kneading and pulverizing method may further include the following classification step, if necessary. Mixing step: A step of mixing at least a binder resin, an ester wax, and a colorant to obtain a mixture. Kneading step: a step of melt-kneading the mixture to obtain a kneaded product. Crushing step: a step of pulverizing the kneaded material to obtain a pulverized material. Classification step: a step of classifying the pulverized material.

[0061] In the mixing step, the raw materials of the toner are mixed to obtain a mixture. In the mixing step, a mixer may be used. The mixer is not particularly limited. In the mixing step, other binder resins and other components may be used as necessary. In the kneading step, the mixture obtained in the mixing step is melt-kneaded to obtain a kneaded product. A kneader may be used in the kneading step. The kneader is not particularly limited. In the pulverization step, the kneaded product obtained in the kneading step is pulverized to obtain a pulverized product. A pulverizer may be used in the pulverization step. As the pulverizer, various pulverizers such as a hammer mill may be used. In addition, the pulverized product obtained by the pulverizer may be further pulverized. As the pulverizer for further pulverizing the pulverized product, various pulverizers may be used. The pulverized product obtained in the pulverization step may be used as it is as toner base particles, or may be used as toner base particles after a classification step as necessary. In the classification step, the pulverized product obtained in the pulverization step is classified. A classifier may be used in the classification step. The classifier is not particularly limited.

[0062] The chemical method will now be described. In the chemical method, a binder resin, an ester wax, and optionally other binder resins and other components are mixed to obtain a mixture. The mixture is then melted and kneaded to obtain a kneaded product. The kneaded product is then pulverized to obtain coarsely granulated medium-sized particles. The medium-sized particles are then mixed with an aqueous medium to prepare a mixture. The mixture is then subjected to mechanical shearing to obtain a fine particle dispersion. Finally, the fine particles are aggregated in the fine particle dispersion to form toner base particles.

[0063] A method for adding external additives will be described (external addition step). The external additive is stirred with the toner base particles, for example, by a mixer. The mixer is preferably equipped with a temperature control function. The temperature at which the external additive is adhered to the toner base particles is not particularly limited, but is preferably, for example, 20 to 35°C. The higher the temperature at which the external additive is adhered to the toner base particles, the easier it is for the titanium oxide to adhere to the toner base particles. Therefore, the adhesion strength A tends to be high.

[0064] The stirring speed when the external additive is attached to the toner base particles is not particularly limited, but is preferably, for example, 800 to 1200 rpm. The higher the stirring speed when the external additive is attached to the toner base particles, the easier it is for the silica to adhere to the toner base particles. Therefore, the adhesion strength B tends to be high.

[0065] When attaching the external additive to the toner base particles, in order to strongly attach the titanium oxide to the toner base particles, it is preferable to first stir the titanium oxide and the toner base particles, and then add silica and stir the mixture. When silica is added after stirring the titanium oxide and the toner base particles, the ratio of the stirring time of silica to the total stirring time is preferably about 50 to 80% of the total stirring time. When this ratio is equal to or greater than the lower limit, it is easy to ensure the stirring time of silica, and the adhesion strength B is easy to increase. When the ratio is equal to or less than the upper limit, the stirring time for the titanium oxide is easily ensured, and the adhesive strength A is easily increased.

[0066] The external additive before stirring may be sieved using a sieving device as necessary. The sieving device is not particularly limited. Various sieving devices can be used.

[0067] A toner cartridge according to an embodiment will be described. The toner cartridge of the embodiment contains the toner of the above-mentioned embodiment. For example, the toner cartridge has a container, and the toner of the embodiment is contained in the container. The container is not particularly limited, and various containers applicable to the image forming apparatus can be used. The toner of the embodiment may be used as a two-component developer in combination with a carrier.

[0068] Hereinafter, an image forming apparatus according to an embodiment will be described with reference to the drawings. FIG. 1 is a diagram showing an example of a schematic structure of an image forming apparatus capable of reusing collected toner. The copier body 101 shown in FIG. 1 comprises an image forming unit 101A provided on one side of the center; a document placement tray 135 provided on the upper surface; a scanner 136 provided below the document placement tray 135; and multiple-stage paper feed cassettes 142, 143 provided on the lower side.

[0069] Image forming unit 101A has a photosensitive drum 102 that is rotatable in the direction of the arrow; a charging charger 103 that charges the surface of photosensitive drum 102; a laser unit 104 that forms an electrostatic latent image on the surface of photosensitive drum 102; a developing device 105 that develops the electrostatic latent image on photosensitive drum 102 with toner; a transfer charger 106 that transfers the toner image on photosensitive drum 102 to paper; a cleaning device 107 that removes residual toner from photosensitive drum 102; and a supply container 108 provided above developing device 105. An electric charger 103, a laser unit 104, a developing device 105, a transfer charger 106, and a cleaning device 107 are provided around the periphery of the photosensitive drum 102 in this order along the direction of rotation of the photosensitive drum 102. The supply container 108 supplies the toner of the embodiment to the developing device 105. The supply container 108 stores the toner of the embodiment.

[0070] Scanner 136 exposes an original on original placement table 135. Scanner 136 has a light source 137 that irradiates light onto the original, a first reflecting mirror 138 that reflects the light reflected from the original in a predetermined direction, a second reflecting mirror 139 and a third reflecting mirror 140 that sequentially reflect the light reflected from first reflecting mirror 138, and a light receiving element 141 that receives the light reflected from third reflecting mirror 140. Paper feed cassettes 142 and 143 feed paper to image forming unit 101A. The paper is transported upward via transport system 144. Transport system 144 has a transport roller pair 145, a registration roller pair 146, a transfer charger 106, a fixing roller pair 147, and a discharge roller pair 148.

[0071] In the image forming apparatus shown in FIG. 1, image formation is carried out, for example, as follows. First, light is irradiated from light source 137 onto an original placed on original placement table 135. The irradiated light is reflected from the original and transmitted in order through first reflecting mirror 138, second reflecting mirror 139, and third reflecting mirror 140 to be received by light receiving element 141, whereby the original image is read. Next, based on the read information of light receiving element 141, laser unit 104 irradiates laser light LB onto the surface of photoconductor drum 102. Here, the surface of the photoconductor drum 102 is negatively charged by an electrostatic charger 103. When the photoconductor drum 102 is irradiated with laser light LB from a laser unit 104, the photoconductor drum 102 is exposed, and the potential of the irradiated portion approaches 0. Therefore, in the area corresponding to the image portion of the document, the surface potential of the photoconductor drum 102 approaches 0 in accordance with the density of the image, and an electrostatic latent image is formed. As the photoconductor drum 102 rotates, the electrostatic latent image attracts toner at a position opposite the developing device 105, forming a toner image. When the toner image is formed, paper is supplied from paper feed cassettes 142 and 143 to a conveying system 144. The paper is aligned by registration rollers 146 and then fed between the transfer charger 106 and the photoconductor drum 102. The toner image on the photoconductor drum 102 is then transferred to the paper. The paper onto which the toner image has been transferred is conveyed to a pair of fixing rollers 147. In the pair of fixing rollers 147, the paper is pressurized and heated, and the toner image is fixed onto the paper. The toner of the embodiment has excellent low-temperature fixing properties when the toner base particles contain a crystalline polyester resin. Therefore, fixing can be performed at, for example, about 140 to 170°C. After fixing, the paper is discharged onto a paper discharge tray 150 via a pair of paper discharge rollers 148. Meanwhile, the toner remaining on the surface of the photoconductor drum 102 without being transferred to the paper is removed by a cleaning device 107. The toner is then returned to the developing device 105 by a recovery mechanism 110 and reused. In the image forming apparatus shown in FIG. 1, when the toner in the developing device 105 is consumed, the toner of the embodiment is newly replenished as fresh toner from a replenishing container 108.

[0072] The developing device 105 will be described with reference to FIGS. The developing device 105 has a recovery mechanism 110 that recovers toner for reuse; a developing container 111 in which a developer including the toner of the embodiment is stored; a developing roller 112 that is rotatably arranged in the developing container 111; a first partition wall 114 and a second partition wall 115 that form a first chamber 116, a second chamber 117, and a third chamber 118 in the developing container 111; a first mixer 120 that is arranged in the first chamber 116; a second mixer 121 that is arranged in the second chamber 117; a third mixer 122 that is arranged in the third chamber 118; a fresh toner receiving section 123 that receives fresh toner supplied from a refill container; a recycled toner receiving section 124; and a toner concentration detector 129.

[0073] The developing device 105 is connected to the cleaning device 107 via a recovery mechanism 110. In the developing device 105, the recovery mechanism 110 is an auger to which the recycled toner is transported. However, the recovery mechanism 110 is not limited to an auger. The cleaning device 107 may be a cleaning blade or a cleaning brush. The developing roller 112 is disposed in a position facing the lower surface of the photosensitive drum. The developing roller 112 supplies developer to the photosensitive drum by rotating.

[0074] A first communication portion 125 is formed on the first end side of the first partition wall 114. A second communication portion 126 is formed on the second end side of the first partition wall 114. A third communication portion 127 and a fourth communication portion 128 are formed in the second partition wall 115. The inside of the developing container 111 is divided into a first chamber 116, a second chamber 117, and a third chamber 118 by a first partition wall 114 and a second partition wall 115. The first chamber 116, the second chamber 117, and the third chamber 118 are formed approximately in parallel along the axial direction of the photosensitive drum 102. Here, on the paper, the direction from the second communication portion 126 to the first communication portion 125 in the first partition wall 114 is defined as a first direction. Also, the direction opposite to the first direction, i.e., the direction from the first communication portion 125 to the second communication portion 126, is defined as a second direction.

[0075] The first mixer 120 rotates to agitate and transport the developer in a first direction and supply it to the developing roller 112. The second mixer 121 and the third mixer 122 agitate and transport the developer in a second direction and send it to the upstream side of the first mixer 120. The second mixer 121 and the third mixer 122 are rotationally driven by a driving means. In the developing device 105, the driving means includes a driving motor 162 as a single driving source, and a driving gear 163 rotated by the driving motor 162. The driving gear 163 is connected to the rotating shaft 151 of the third mixer 122 via a large-diameter power transmission gear 164. In addition, the large-diameter power transmission gear 164 is connected to the rotating shaft 121a of the second mixer 121 via a small-diameter power transmission gear 165.

[0076] In the developing device 105 having the configuration described above, the developer transport speed by the third mixer 122 is lower than the developer transport speed by the second mixer 121. Therefore, the developer transport time by the third mixer 122 is longer than the developer transport time by the second mixer 121. In another embodiment, the second and third mixers 121, 122 may be rotated and driven separately by a plurality of drive motors with different rotation speeds. Also, the third mixer 122 may be provided with a reverse feed blade that transports the collected toner in a direction opposite to the second direction. Whichever method is adopted, the transport speed of the collected toner by the third mixer 122 can be made lower than the transport speed of the developer by the second mixer 121.

[0077] Next, the developing operation of the developing device 105 will be described with reference to FIGS. In the developing container 111, the developer is stirred and transported in a first direction by the rotation of the first mixer 120, and is supplied to the developing roller 112. Thereafter, the developer is supplied to the electrostatic latent image on the photoconductor drum 102 by the rotation of the developing roller 112, and the electrostatic latent image is visualized.

[0078] The developer discharged from the first mixer 120 is guided into the second chamber 117 via the first communication portion 125. Thereafter, in the second chamber 117, the developer is transported in the direction of the arrow (second direction) by the rotation of the second mixer 121. The developer discharged by the second mixer 121 is sent to the upstream side of the first mixer 120 via the second communication portion 126, and is transported so as to circulate between the first mixer 120 and the developer.

[0079] A portion of the developer transported by the second mixer 121 is sent from the third communication part 127 into the third chamber 118 and transported in the direction of the arrow (second direction). The developer is sent again into the second chamber 117 from the fourth communication part 128 and is agitated and transported by the second mixer 121. The developer is then sent to the upstream side of the first mixer 120 via the second communication part 126. Here, the toner concentration of the developer stirred and transported by the second mixer 121 is detected by a toner concentration detector 129. When the toner concentration detected by the toner concentration detector 129 falls below a predetermined value, the toner of the embodiment is replenished from the replenishing container 108. This toner falls into a fresh toner receiving portion 123 of the developing container 111. The fresh toner is stirred and transported in the direction of the arrow (second direction) by the rotation of the second mixer 121, and is sent to the upstream side of the first mixer 120.

[0080] The recovered toner recovered from the cleaning device 107 by the recovery mechanism 110 falls into the recycled toner receiving section 124. The recovered toner is transported in the second direction by the rotation of the third mixer 122. Here, the developer guided from the third communicating section 127 into the third chamber 118 is once stirred and transported toward the recycled toner receiving section 124 side as shown by the arrow a by the rotation of the reverse feed blade 153 of the third mixer 122. Thereafter, the developer together with the recovered toner is stirred and transported in the second direction as shown by the arrow b by the rotation of the forward feed blade 152. The recovered toner is sent to the upstream side of the first mixer 120 via the fourth communicating section 128 and the second communicating section 126 in this order. Some of the developer and recovered toner are sent downstream in the transport direction without being sent into the second chamber 117 through the fourth communicating portion 128. Such developer and recovered toner are sent backwards by the rotation of the reverse feed blade 155 and returned to the fourth communicating portion 128, and are sent to the second chamber 117 through the fourth communicating portion 128.

[0081] FIG. 4 shows an example of an image forming apparatus to which a developer containing the toner of the embodiment is applied. The image forming apparatus shown in Fig. 4 is a type that fixes a toner image. However, the image forming apparatus according to the embodiment is not limited to this type. The image forming apparatus according to the other embodiment may be, for example, an inkjet type. The image forming apparatus 1 shown in Fig. 4 is a four-tandem color copier MFP. The image forming apparatus 1 includes a scanner unit 2, a paper discharge unit 3, a paper feed cassette 4, an intermediate transfer belt 10, four image forming stations 11Y, 11M, 11C, and 11K arranged along the running direction S of the intermediate transfer belt 10, a secondary transfer roller 27, a fixing device 30, and a manual feed mechanism 31.

[0082] The intermediate transfer belt 10 is wound around and supported by a driven roller 20 and a backup roller 21. In addition to the driven roller 20 and the backup roller 21, a desired tension is applied to the intermediate transfer belt 10 by a first tension roller 22, a second tension roller 23, and a third tension roller 24.

[0083] The image forming stations 11Y, 11M, 11C, and 11K each have a photoconductor drum 12Y, 12M, 12C, and 12K in contact with the intermediate transfer belt 10, respectively. Arranged around the photoconductor drums 12Y, 12M, 12C, 12K are electrostatic chargers 13Y, 13M, 13C, 13K; developing devices 14Y, 14M, 14C, 14K; photoconductor cleaning devices 16Y, 16M, 16C, 16K; and primary transfer rollers 18Y, 18M, 18C, 18K.

[0084] The electric chargers 13Y, 13M, 13C, and 13K negatively charge the surfaces of the photoconductor drums 12Y, 12M, 12C, and 12K. Between the electric chargers 13Y, 13M, 13C, and 13K and the developing devices 14Y, 14M, 14C, and 14K, the laser exposure device 17 irradiates the photoconductor drums 12Y, 12M, 12C, and 12K with exposure light. Then, electrostatic latent images are formed on the photoconductor drums 12Y, 12M, 12C, and 12K. The developing devices 14Y, 14M, 14C, and 14K each have a two-component developer consisting of yellow (Y), magenta (M), cyan (C), and black (K) toner and a carrier. The developing devices 14Y, 14M, 14C, and 14K supply the toner to the electrostatic latent images on the photoconductor drums 12Y, 12M, 12C, and 12K, respectively. In this manner, the image forming stations 11Y, 11M, 11C, and 11K form monochrome images of yellow (Y), magenta (M), cyan (C), and black (K), respectively.

[0085] The primary transfer rollers 18Y, 18M, 18C, and 18K are provided on the intermediate transfer belt 10 at positions facing the photoconductor drums 12Y, 12M, 12C, and 12K, respectively. The primary transfer rollers 18Y, 18M, 18C, and 18K are used to primarily transfer the toner images on the photoconductor drums 12Y, 12M, 12C, and 12K onto the intermediate transfer belt 10. The primary transfer rollers 18Y, 18M, 18C, and 18K are each a conductive roller, and a primary transfer bias voltage is applied to each of the primary transfer rollers 18Y, 18M, 18C, and 18K.

[0086] The secondary transfer roller 27 is disposed at a transfer position where the intermediate transfer belt 10 is supported by the backup roller 21. The backup roller 21 is a conductive roller. A predetermined secondary transfer bias is applied to the backup roller 21. When a sheet of paper to be printed passes between the intermediate transfer belt 10 and the secondary transfer roller 27, the toner image on the intermediate transfer belt 10 is secondarily transferred onto the sheet of paper. After the secondary transfer is completed, the intermediate transfer belt 10 is cleaned by a belt cleaner 10a.

[0087] The paper feed cassette 4 is provided below the laser exposure device 17. The paper feed cassette 4 supplies the sheet paper P1 toward the secondary transfer roller 27. Between the paper feed cassette 4 and the secondary transfer roller 27, a pickup roller 4a, a separation roller 28a, a conveyance roller 28b, and a registration roller pair 36 are provided. The manual feed mechanism 31 is provided on one side of the image forming apparatus 1. The manual feed mechanism 31 is for manually feeding the sheet paper P2. In the manual feed mechanism 31, a manual feed pickup roller 31b and a manual feed separation roller 31c are provided between a manual feed tray 31a and a pair of registration rollers 36.

[0088] A media sensor 39 that detects the type of sheet paper is disposed on the vertical transport path 35 along which the sheet paper is transported from the paper feed cassette 4 or the manual feed tray 31a. The image forming apparatus 1 can control the transport speed, transfer conditions, fixing conditions, etc. of the sheet paper based on the detection results of the media sensor 39. The sheet paper is transported along the vertical transport path 35 through a pair of registration rollers 36 and a secondary transfer roller 27 to the fixing device 30.

[0089] The fixing device 30 has a fixing belt 53 wound around a pair of a heating roller 51 and a driving roller 52, and an opposing roller 54 disposed opposite the heating roller 51 with the fixing belt 53 interposed therebetween. The fixing device 30 can heat the fixing belt 53 at a portion in contact with the heating roller 51. The fixing device 30 then applies heat and pressure to the sheet paper onto which the toner image has been transferred between the fixing belt 53 and the opposing roller 54, thereby fixing the toner image to the sheet paper. The toner according to the embodiment has excellent low-temperature fixing properties when the toner base particles contain a crystalline polyester resin, and can be fixed at a temperature of, for example, about 140 to 170°C.

[0090] A gate 33 is provided downstream of the fixing device 30. The sheet paper is distributed to the discharge rollers 41 or the re-conveying unit 32. The sheet paper distributed to the discharge rollers 41 is discharged to the discharge section 3. On the other hand, the sheet paper distributed to the re-conveying unit 32 is guided again toward the secondary transfer roller 27.

[0091] In the image forming apparatus 1 shown in Fig. 4, the image forming station 11Y has a photoconductor drum 12Y and a process member integrally, and is provided so as to be detachable from the main body of the image forming apparatus. The process members include a charger 13Y, a developing device 14Y, and a photoconductor cleaning device 16Y. However, in other embodiments, the image forming stations 11Y, 11M, 11C, and 11K may be detachable from the image forming apparatus individually, or may be detachable from the image forming apparatus as an integrated image forming unit 11.

[0092] The toner of the embodiment may be applied to an image forming apparatus in which the developing device 14Y of the image forming apparatus shown in Fig. 4 is modified. Fig. 5 shows an example of a modified developing device that can be applied to the image forming apparatus of Fig. 4. The developing device 64Y shown in FIG. 5 contains a two-component developer consisting of yellow toner and a carrier. The developing device 64Y has a toner concentration sensor Q. The toner concentration sensor Q detects a decrease in toner concentration. When the developing device 64Y detects a decrease in concentration, it replenishes yellow toner from a toner cartridge (not shown). In this way, the developing device 64Y can maintain a constant toner concentration. In addition, the developing device 64Y can be replenished with carrier from a toner cartridge (not shown) via a developer supply port 64Y1, and the developing device 64Y can discharge the developer by overflow from a developer discharge port 64Y2 in an amount equal to the amount of developer replenished. In this way, in the developing device 64Y, the amount of developer is maintained constant, and old, deteriorated carrier is gradually replaced with new carrier. Like developing device 14Y, developing devices 14M, 14C, and 14K in FIG. 4 may be modified to developing devices 64M, 64C, and 64K (not shown) similar to developing device 64Y, except that magenta toner, cyan toner, and black toner, respectively, are used instead of yellow toner.

[0093] The toner according to at least one of the embodiments described above is less likely to cause image defects even when reused. EXAMPLES

[0094] The following examples are provided to more specifically explain the embodiments.

[0095] The preparation of ester wax A used in the examples will be described below. Into a four-neck flask equipped with a stirrer, a thermocouple, and a nitrogen inlet tube, 80 parts by mass of at least three or more long-chain alkyl carboxylic acids and 20 parts by mass of at least two or more long-chain alkyl alcohols were charged. Under a nitrogen gas flow, an esterification reaction was carried out at 220°C to obtain a reaction product. A mixed solvent of toluene and ethanol was added to the obtained reaction product to dissolve the reaction product. Furthermore, an aqueous sodium hydroxide solution was added to the flask and stirred at 70°C for 30 minutes. After standing for another 30 minutes, the contents of the flask were separated into an organic layer and an aqueous layer, and the aqueous layer was removed from the contents. Thereafter, ion-exchanged water was added to the flask and stirred at 70°C for 30 minutes. The flask was left standing for 30 minutes, the contents in the flask were separated into an aqueous layer and an organic layer, and the aqueous layer was removed from the contents. This operation was repeated five times. The solvent was distilled off from the organic layer of the contents in the flask under reduced pressure conditions to obtain ester wax A.

[0096] The long-chain alkyl carboxylic acids used were as follows: Palmitic acid (C 16 H 32 O2) Stearic acid (C 18 H 36 O2) Arachidic acid (C 20 H 40 O2) Behenic acid (C 22 H 44 O2) Lignoceric acid (C 24 H 48 O2) Cerotin acid (C 26 H 52 O2) Montanic acid (C 28 H 56 O2)

[0097] The long-chain alkyl alcohols used were as follows: Palmityl alcohol (C 16 H 34 O) Stearyl alcohol (C 18 H 38 O) Arachidyl alcohol (C 20 H 42 O) Behenyl alcohol (C 22 H 46 O) Lignoceryl alcohol (C 24 H 50 O) Seryl alcohol (C 26 H 54 O) Montanyl alcohol (C 28 H 58 O)

[0098] A method for measuring the carbon number distribution (proportion of ester compounds with each carbon number) of ester compounds constituting the ester wax will be described. 0.5 g of the toner of each example was weighed and placed in an Erlenmeyer flask. Next, 2 mL of methylene chloride was added to the Erlenmeyer flask to dissolve the toner. Furthermore, 4 mL of hexane was added to the Erlenmeyer flask to obtain a mixed liquid. The mixed liquid was filtered to separate into a filtrate and an insoluble matter. The solvent was distilled off from the filtrate under a nitrogen stream to obtain a precipitate. For this precipitate, the carbon number distribution of the ester compound in the ester wax extracted from the toner was measured.

[0099] The proportion of ester compounds with each carbon number was measured using an FD-MS "JMS-T100GC (manufactured by JEOL Ltd.)" under the following measurement conditions. Sample concentration: 1 mg / ml (solvent, chloroform). Cathode voltage:-10kv. Spectral recording interval: 0.4 s. Measurement mass range (m / z): 10 to 2000.

[0100] The total ionic strength of the ester compounds with each carbon number obtained in the measurement was set to 100. The relative value of the ionic strength of the ester compound with each carbon number to the total was calculated. The relative value was taken as the proportion of the ester compound with each carbon number in the ester wax. The number of carbon atoms in the ester compound with the maximum relative value was designated as C l It was decided.

[0101] The analytical methods for the first and second monomer groups will be described. Methanolysis reaction was carried out for 3 hours at 70°C for 1 g of each ester wax. Mass spectrometry was carried out on the products after the methanolysis reaction to determine the content of long-chain alkyl carboxylic acids with each carbon number and the content of long-chain alkyl alcohols with each carbon number.

[0102] A method for measuring the carbon number distribution (proportion of carboxylic acids with each carbon number) of the carboxylic acids constituting the first monomer group will be described. The proportion of carboxylic acids with each carbon number was measured using an FD-MS "JMS-T100GC (manufactured by JEOL Ltd.)" under the following measurement conditions. Sample concentration: 1 mg / ml (solvent, chloroform). Cathode voltage:-10kv. Spectral recording interval: 0.4 s. Measurement mass range (m / z): 10 to 2000.

[0103] The sum of the ionic intensities of the carboxylic acids with each carbon number obtained in the measurement was set to 100. The relative values ​​of the ionic intensities of the carboxylic acids with each carbon number to the total were calculated. The relative values ​​were taken as the proportions of the carboxylic acids with each carbon number in the ester wax. The number of carbon atoms in the carboxylic acid with the maximum relative value was designated as C n It was decided.

[0104] A method for measuring the carbon number distribution (proportion of alcohols with each carbon number) of the alcohols constituting the second monomer group will be described. The proportion of alcohols with each carbon number was measured using an FD-MS "JMS-T100GC (manufactured by JEOL Ltd.)" under the following measurement conditions. Sample concentration: 1 mg / ml (solvent, chloroform). Cathode voltage:-10kv. Spectral recording interval: 0.4 s. Measurement mass range (m / z): 10 to 2000.

[0105] The sum of the ion intensities of the alcohols with each carbon number obtained in the measurement was set to 100. The relative value of the ion intensity of the alcohol with each carbon number to the total was calculated. The relative value was taken as the proportion of the alcohol with each carbon number in the ester wax. The carbon number in the alcohol with the carbon number that gave the maximum relative value was designated as C m It was decided.

[0106] The ester wax A used in each example will be described below. The carbon number C of the ester compound with the maximum content of ester wax A l The carbon number C relative to 100% by mass of ester wax was 44. l The proportion of the ester compound was 70% by mass. The number of types of carboxylic acids in the first monomer group was 4. The maximum content of the carboxylic acid in the first monomer group was C n The carbon number C relative to 100% by mass of the first monomer group was 22. n The proportion of the carboxylic acid having 18 or less carbon atoms relative to 100% by mass of the first monomer group was 3% by mass. The number of types of alcohol in the second monomer group was 3. The carbon number C of the alcohol with the maximum content in the second monomer group was m The carbon number C relative to 100% by mass of the second monomer group was 22. m The proportion of the alcohols having 18 or less carbon atoms relative to 100 mass % of the second monomer group was 15 mass %. The carbon number distribution of ester wax A had only one maximum peak in the region of carbon numbers 43 or more.

[0107] The crystalline polyester resin used in each example had a mass average molecular weight Mw of 9,500 and a melting point of 100°C. The amorphous polyester resin used in each example had a mass average molecular weight of 20,000 and a melting point of 110°C. D of strontium titanate used in each example 50 The D of the titanium oxide used in each example was 20 nm. 50 was 20 nm.

[0108] The silica used in each example is as follows: Silica A: (hydrophobic silica, D 50 :30nm) Silica B: (hydrophobic silica, D 50 :90nm) Silica C: (hydrophobic silica, D 50 :100nm)

[0109] The toner of Example 1 was prepared as follows. First, the raw materials for the toner base particles were put into a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.) and mixed. The mixture of raw materials for the toner base particles was then melted and kneaded in a twin-screw extruder. After cooling the melted and kneaded product, it was coarsely pulverized in a hammer mill. The coarsely pulverized product was then finely pulverized in a jet pulverizer. The finely pulverized product was classified to obtain toner base particles. The D of the toner base particles 50 was 8.5 μm. The composition of the raw materials for the toner base particles is shown below. Crystalline polyester resin 5 parts by mass Amorphous polyester resin 84 parts by weight Ester wax A 5 parts by weight Carbon black 5 parts by weight Charge control agent (polysaccharide inclusion compound containing Al and Mg) 1 part by mass

[0110] Next, the temperature of a Henschel mixer with a temperature control function was set to 35° C. After the toner base particles were added to the stirring section, 0.5 parts by mass of titanium oxide was added per 100 parts by mass of the toner base particles, and the mixture was stirred for 5 minutes at 35° C. and 900 rpm. The stirring was stopped, and 2.5 parts by mass of silica A and 0.6 parts by mass of silica B per 100 parts by mass of the toner base particles were added to the stirring section, and the mixture was further stirred for 10 minutes at 35° C. and 900 rpm, to obtain the toner of Example 1.

[0111] The toner of Example 2 was prepared as follows. First, the toner base particles of Example 2 were produced in the same manner as in Example 1, except that the composition of the raw materials for the toner base particles was changed as follows. 50 was 8.5 μm. Crystalline polyester resin 5 parts by mass Amorphous polyester resin 84 parts by weight Ester wax A 5 parts by weight Carbon black 5 parts by weight Charge control agent (polysaccharide inclusion compound containing Al and Mg) 1 part by mass

[0112] Next, the temperature of a Henschel mixer with a temperature control function was set to 31° C. After the toner base particles were added to the stirring section, 0.4 parts by mass of titanium oxide was added per 100 parts by mass of the toner base particles, and the mixture was stirred for 4 minutes at 31° C. and 900 rpm. The stirring was stopped, and 2.5 parts by mass of silica A and 0.4 parts by mass of silica B per 100 parts by mass of the toner base particles were added to the stirring section, and the mixture was further stirred for 8 minutes at 31° C. and 900 rpm, to obtain the toner of Example 2.

[0113] The toner of Example 3 was prepared as follows. First, the toner base particles of Example 3 were produced in the same manner as in Example 1, except that the composition of the raw materials for the toner base particles was changed as follows. 50 was 8.5 μm. Crystalline polyester resin 5 parts by mass Amorphous polyester resin 84 parts by weight Ester wax A 5 parts by weight Carbon black 5 parts by weight Charge control agent (polysaccharide inclusion compound containing Al and Mg) 1 part by mass

[0114] Next, the temperature of a Henschel mixer with a temperature control function was set to 30° C. After the toner base particles were added to the stirring section, 0.5 parts by mass of titanium oxide was added per 100 parts by mass of the toner base particles, and the mixture was stirred for 5 minutes at 30° C. and 900 rpm. The stirring was stopped, and 2.5 parts by mass of silica A and 0.6 parts by mass of silica C per 100 parts by mass of the toner base particles were added to the stirring section, and the mixture was further stirred for 9 minutes at 30° C. and 900 rpm, to obtain the toner of Example 3.

[0115] The toner of Example 4 was prepared as follows. First, the toner base particles of Example 4 were produced in the same manner as in Example 1, except that the composition of the raw materials for the toner base particles was changed as follows. 50 was 8.5 μm. Crystalline polyester resin 5 parts by mass Amorphous polyester resin 84 parts by weight Ester wax A 5 parts by weight Carbon black 5 parts by weight Charge control agent (polysaccharide inclusion compound containing Al and Mg) 1 part by mass

[0116] Next, the temperature of the Henschel mixer with a temperature control function was set to 32° C. After the toner base particles were added to the stirring section, 0.5 parts by mass of strontium titanate was added per 100 parts by mass of the toner base particles, and the mixture was stirred for 4 minutes and 30 seconds under the conditions of 32° C. and 900 rpm. The stirring was stopped, and 2.5 parts by mass of silica A and 0.5 parts by mass of silica C per 100 parts by mass of the toner base particles were added to the stirring section, and the mixture was further stirred for 8 minutes and 30 seconds under the conditions of 32° C. and 900 rpm, to obtain the toner of Example 4.

[0117] The toner of Example 5 was prepared as follows. First, the toner base particles of Example 5 were produced in the same manner as in Example 1, except that the composition of the raw materials for the toner base particles was changed as follows. 50 was 8.5 μm. Crystalline polyester resin 5 parts by mass Amorphous polyester resin 84 parts by weight Ester wax A 5 parts by weight Carbon black 5 parts by weight Charge control agent (polysaccharide inclusion compound containing Al and Mg) 1 part by mass

[0118] Next, the temperature of a Henschel mixer with a temperature control function was set to 30° C. After the toner base particles were added to the stirring section, 0.4 parts by mass of titanium oxide was added per 100 parts by mass of the toner base particles, and the mixture was stirred for 5 minutes at 30° C. and 900 rpm. The stirring was stopped, and 2.5 parts by mass of silica A and 0.5 parts by mass of silica C per 100 parts by mass of the toner base particles were added to the stirring section, and the mixture was further stirred for 8 minutes at 30° C. and 900 rpm, to obtain the toner of Example 5.

[0119] The toner of Comparative Example 1 was produced as follows. First, the toner base particles of Comparative Example 1 were produced in the same manner as in Example 1, except that the composition of the raw materials for the toner base particles was changed as follows. 50 was 8.5 μm. Crystalline polyester resin 5 parts by mass Amorphous polyester resin 84 parts by weight Ester wax A 5 parts by weight Carbon black 5 parts by weight Charge control agent (polysaccharide inclusion compound containing Al and Mg) 1 part by mass

[0120] Next, the temperature of a Henschel mixer with a temperature control function was set to 30° C. After the toner base particles were added to the stirring section, 0.4 parts by mass of titanium oxide was added per 100 parts by mass of the toner base particles, and the mixture was stirred for 5 minutes at 30° C. and 800 rpm. The stirring was stopped, and 2.5 parts by mass of silica A and 0.4 parts by mass of silica B per 100 parts by mass of the toner base particles were added to the stirring section, and the mixture was further stirred for 8 minutes at 30° C. and 800 rpm, to obtain the toner of Comparative Example 1.

[0121] The toner of Comparative Example 2 was produced as follows. First, the toner base particles of Comparative Example 2 were produced in the same manner as in Example 1, except that the composition of the raw materials for the toner base particles was changed as follows. 50 was 8.5 μm. Crystalline polyester resin 5 parts by mass Amorphous polyester resin 84 parts by weight Ester wax A 5 parts by weight Carbon black 5 parts by weight Charge control agent (polysaccharide inclusion compound containing Al and Mg) 1 part by mass

[0122] Next, the temperature of a Henschel mixer with a temperature control function was set to 34° C. After the toner base particles were added to the stirring section, 0.4 parts by mass of titanium oxide was added per 100 parts by mass of the toner base particles, and the mixture was stirred for 5 minutes at 34° C. and 900 rpm. The stirring was stopped, and 2.5 parts by mass of silica A and 0.6 parts by mass of silica B per 100 parts by mass of the toner base particles were added to the stirring section, and the mixture was further stirred for 10 minutes at 34° C. and 900 rpm, to obtain a toner of Comparative Example 2.

[0123] The toner of Comparative Example 3 was produced as follows. First, the toner base particles of Comparative Example 3 were produced in the same manner as in Example 1, except that the composition of the raw materials for the toner base particles was changed as follows. 50 was 8.5 μm. Crystalline polyester resin 5 parts by mass Amorphous polyester resin 84 parts by weight Ester wax A 5 parts by weight Carbon black 5 parts by weight Charge control agent (polysaccharide inclusion compound containing Al and Mg) 1 part by mass

[0124] Next, the temperature of a Henschel mixer with a temperature control function was set to 33° C. After the toner base particles were added to the stirring section, 0.5 parts by mass of titanium oxide was added per 100 parts by mass of the toner base particles, and the mixture was stirred for 5 minutes at 33° C. and 900 rpm. The stirring was stopped, and 2.5 parts by mass of silica A and 0.5 parts by mass of silica B per 100 parts by mass of the toner base particles were added to the stirring section, and the mixture was further stirred for 9 minutes at 33° C. and 900 rpm, to obtain a toner of Comparative Example 3.

[0125] The toner of Comparative Example 4 was produced as follows. First, the toner base particles of Comparative Example 4 were produced in the same manner as in Example 1, except that the composition of the raw materials for the toner base particles was changed as follows. 50 was 8.5 μm. Crystalline polyester resin 5 parts by mass Amorphous polyester resin 84 parts by weight Ester wax A 5 parts by weight Carbon black 5 parts by weight Charge control agent (polysaccharide inclusion compound containing Al and Mg) 1 part by mass

[0126] Next, the temperature of the Henschel mixer with a temperature control function was set to 33° C. After the toner base particles were added to the stirring section, 0.4 parts by mass of strontium titanate was added per 100 parts by mass of the toner base particles, and the mixture was stirred for 4 minutes at 33° C. and 900 rpm. The stirring was stopped, and 2.5 parts by mass of silica A and 0.5 parts by mass of silica C per 100 parts by mass of the toner base particles were added to the stirring section, and the mixture was further stirred for 10 minutes at 33° C. and 900 rpm, to obtain the toner of Comparative Example 4.

[0127] The toner of Comparative Example 5 was produced as follows. First, the toner base particles of Comparative Example 5 were produced in the same manner as in Example 1, except that the composition of the raw materials for the toner base particles was changed as follows. 50 was 8.5 μm. Crystalline polyester resin 5 parts by mass Amorphous polyester resin 84 parts by weight Ester wax A 5 parts by weight Carbon black 5 parts by weight Charge control agent (polysaccharide inclusion compound containing Al and Mg) 1 part by mass

[0128] Next, the temperature of a Henschel mixer with a temperature control function was set to 30° C. After the toner base particles were added to the stirring section, 0.3 parts by mass of titanium oxide was added per 100 parts by mass of the toner base particles, and the mixture was stirred for 6 minutes at 30° C. and 800 rpm. The stirring was stopped, and 2.5 parts by mass of silica A and 0.3 parts by mass of silica C per 100 parts by mass of the toner base particles were added to the stirring section, and the mixture was further stirred for 8 minutes at 30° C. and 800 rpm, to obtain a toner of Comparative Example 5.

[0129] The method for measuring adhesive strength A will be explained. A sucrose solution was prepared by dissolving 227.7 g of sucrose in 113.3 g of ion-exchanged water. This sucrose solution and 25.53 g of a 10% aqueous solution of coconut detergent were placed in a 250 mL plastic bottle and thoroughly mixed to prepare a dispersion medium. 11 g of the toner of each example was added to the plastic bottle and left to stand until the toner naturally settled, to prepare a pre-treatment dispersion liquid. Next, the pre-treatment dispersion liquid was shaken in a Turbula mixer at 25°C and 200 rpm for 5 minutes to promote the detachment of titanium oxide from the surface of the toner base particles. Then, centrifugation was performed at 3700 rpm for 30 minutes. This centrifugation separated the detached titanium oxide particles from the toner carrying titanium oxide remaining on the surface of the toner base particles. Thereafter, the toner with the remaining titanium oxide particles was collected by suction filtration, washed with water, and dried to obtain particles A. 5.0 g of these particles A were molded into pellets using a molding machine. The pellets were analyzed for the X-ray intensity of titanium (I a2 On the other hand, the toner of each example was formed into pellets without the titanium oxide removal treatment, and the X-ray intensity of titanium (I a1 Based on these measured values, the adhesive strength A was calculated using the following formula (1). Adhesion strength A = (I a2 / I a1 )×100 Equation (1)

[0130] I a1 , I a2 The measurement conditions are as follows: Rhodium target X-ray tube Tube voltage 50kV ·Tube current 50μA X-ray detector: SC detector Angle range (deg): 10-90 ·Speed(deg / min):20 Step angle (deg): 0.1

[0131] The method for measuring adhesive strength B will be described. (1) 11 g of toner of each example, 56.8 g of ion-exchanged water, and 12.8 g of surfactant were added to a 100 ml beaker and mixed. The mixture was stirred with a magnetic stirrer until there was no toner layer on the liquid surface, to obtain a dispersion. (2) The obtained dispersion was subjected to ultrasonic treatment using an ultrasonic cleaner (ASONE US-1R). The ultrasonic treatment conditions were 25°C, 28 kHz, and 55 W. The dispersion after ultrasonic treatment was poured into two centrifuge tubes, and ion-exchanged water was added to each tube so that the total liquid volume in each tube was 45 ml. (3) Next, these two centrifuge tubes were centrifuged at 1000 rpm for 15 minutes. A centrifuge (HSIANGTAI CN-2060) was used for the centrifugation. After that, the supernatant liquid from each of the two centrifuge tubes was removed by decantation, the silica that had been detached from the surface of the toner base particles was removed, and the toner carrying the silica remaining on the surface of the toner base particles was recovered. Ion-exchanged water was then added to each centrifuge tube until the total liquid volume in each tube was 45 ml. (4) The above scanning in (3) was repeated twice. Thereafter, 100 ml of ion-exchanged water was added to the toner carrying the silica remaining on the surface of the toner base particles to wash them, filtered through filter paper (ADVANTEC GC90), and vacuum-dried for 8 hours to obtain particles B. 5.0 g of these particles B were molded into pellets using a molding machine. The pellets were analyzed for the X-ray intensity of silicon (I b2 On the other hand, the toner of each example was molded into pellets without the titanium oxide removal treatment, and the X-ray intensity of silicon (I b1 ) was measured. Based on these measured values, the adhesive strength B was calculated using the following formula (2). Adhesion strength B = (I b2 / I b1 )×100 Formula (2)

[0132] I b1 , I b2 The measurement conditions are as follows: Rhodium target X-ray tube Tube voltage 50kV ·Tube current 50μA X-ray detector: FPC detector Angle range (deg): 106-112 ·Speed(deg / min):20 Step angle (deg): 0.1

[0133] D 50 The measurement method will be explained. Using a laser diffraction particle size distribution analyzer (Shimadzu Corporation (SALD7000)), the volume average primary particle diameter was measured. 50 was measured.

[0134] The developer of the embodiment will be described. 8.5 parts by mass of the toner of each example was mixed with 100 parts by mass of the ferrite carrier in a Turbula mixer to obtain a developer of each example. The surface of the ferrite carrier was coated with a silicone resin having an average particle size of 40 μm.

[0135] The method for evaluating fogging will be described. A commercially available e-studio5018A (manufactured by Toshiba Tec) was used. The e-studio5018A is equipped with a toner recycling system. While this recycling system was running, 100,000 A4 originals with a print rate of 2.0% were continuously copied. If the fog value of the blank copy image was maintained at less than 2.0, it was evaluated as passing (◯). If the fog value of the blank copy image was 2.0 or more, it was evaluated as failing (×).

[0136] The method for evaluating white streaks will be described. Using a commercially available e-studio5018A (manufactured by Toshiba Tec), the temperature of the developer Dc-Sl was adjusted so that it was saturated at 47°C. Then, while operating the recycle system, 30,000 sheets were printed double-sided in a hot and humid environment, and the temperature of the developer Dc-Sl was adjusted to maintain 47°C by adjusting the airflow of the cooling fan. Next, the image density difference after printing 30,000 sheets was measured. When this image density difference was less than 0.8, it was evaluated as pass (◯). When the image density difference was 0.8 or more, it was evaluated as fail (×). White streaks tend to occur after the image forming device is left in a stopped state. For example, white streaks tend to occur when the image forming device is used in the early morning.

[0137] [Table 1]

[0138] The evaluation results of the toners of the respective examples are shown in Table 1. The toners of Examples 1 to 5 were both within the specific ranges for adhesion strength A and adhesion strength B. In this case, both the fogging and white streaks were acceptable. In contrast to this, in the toners of Comparative Examples 1 to 5, neither fog nor white streaks reached the pass standard at the same time.

[0139] Although some embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope of the invention and its equivalents described in the claims, as well as in the scope and spirit of the invention. [Explanation of symbols]

[0140] 1...image forming apparatus, 2...scanner section, 3...paper discharge section, 4...paper feed cassette, 10...intermediate transfer belt, 11Y, 11M, 11C, 11K...image forming station, 12Y, 12M, 12C, 12K...photoconductor drum, 13Y, 13M, 13C, 13K...electric charger, 14Y, 14M, 14C, 14K...developing device, 30...fixing device, 31...manual feed mechanism, 64Y...developing device, 101...copying machine main body, 102...photoconductor drum, 103...electric charger , 104...laser unit, 105...developing device, 106...transfer charger, 107...cleaning device, 108...supply container, 110...recovery mechanism, 111...developing container, 112...developing roller, 114, 115...first and second partition materials, 116-118...first to third chambers, 120-122...first to third mixers, 123...fresh toner receiving section, 124...recycled toner receiving section, 125-128...first to fourth communicating sections, 129...toner concentration detector.

Claims

1. The toner comprises a toner base particle and an external additive attached to the surface of the toner base particle, the toner base particles contain a binder resin, an ester wax, and a colorant, the ester wax is a condensation polymer of a first monomer group consisting of at least three kinds of carboxylic acids and a second monomer group consisting of at least two kinds of alcohols, The carbon number distribution of the ester wax has only one maximum peak in a region having 43 or more carbon atoms, The external additive contains titanium oxide and silica, The adhesion strength A of the external additive to the toner base particles calculated by the following formula (1) is 90 to 100%, The toner has an adhesion strength B of the external additive to the toner base particles, calculated by the following formula (2), of 50 to 80%. Adhesion strength A = (I a2 / I a1 )×100 Formula (1) Adhesion strength B = (I b2 / I b1 )×100 Formula (2) In formula (1), I a1 is the titanium X-ray intensity measured for the toner; I a2 is the X-ray intensity of titanium measured for particle A obtained by method A described below. Method A: The aqueous liquid containing the toner and water is shaken for 5 minutes under conditions of 25° C. and 200 rpm, the external additives that have been desorbed are removed by centrifugation, and the particles obtained by drying are designated as particles A. In formula (2), I b1 is the X-ray intensity of silicon measured for the toner; I b2 is the X-ray intensity of silicon measured for particles B obtained by method B described below. Method B: An aqueous liquid containing the toner and water is subjected to ultrasonic treatment under conditions of 25° C., 28 kHz, and 55 W. The external additives that have been desorbed are removed by centrifugation. The particles obtained by drying are designated as particles B.

2. The toner according to claim 1 , wherein at least a portion of the binder resin is a crystalline polyester resin.

3. A toner cartridge containing the toner according to claim 1 or 2.

4. An image forming apparatus containing the toner according to claim 1 or 2.

Citation Information

Patent Citations

  • Image forming method and toner

    JP2002214823A

  • Image forming method and toner

    JP2002296829A

  • Toner and developer for electrostatic image development, image forming apparatus, process cartridge using the same and image forming method

    JP2006058502A

  • Image forming apparatus and image forming method

    JP2006235588A

  • Toner, developer, and image forming apparatus

    JP2014178531A